Sustainability, Natural Gas Consumption, and Environmental Pollution in the Period of Industry 4.0 in Turkey: MS-Granger Causality and Fourier Granger Causality Analysis - Bildirici, Melike E.; Genc, Sema Yilmaz; Boztuna, Salih (MDPI, 2023)
The effects of environmental pollution and Industry 4.0 on a sustainable environment are the main topic of this study, which may be regarded as a complement to the literature on energy and the environment. The paper aims to investigate the relation between Industry 4.0 (I4.0) and environmental sustainability, which is very important for policymakers, practitioners, and company executives in the period of Industry 4.0 in Turkey. To this end, natural gas consumption and technology patents as control variables of Industry 4.0, in addition to the variables of environmental pollution and economic growth, were selected during the period of 1988 to 2022 using Markov switching VAR (MS-VAR), Markov switching Granger causality (MS-GC), Fourier VAR (FVAR), and Granger causality (FGC) techniques. The reason for covering the period starting in 1988 is its recognition as the beginning of the Industry 4.0 era with AutoIDLab in 1988. According to the causality results, there was unidirectional causality running from technology patents to environmental pollution in the results of both MS-GC and FGC. However, the directions of causality between natural gas consumption and environmental pollution, and between economic growth and environmental pollution differed between regimes in the MS-GC model. Bidirectional causality was determined between economic growth and environmental pollution in the first MS-GC regime. However, in the second regime, unidirectional causality from economic growth to environmental pollution was determined. The causality direction determined by Fourier causality gave the same result with the second regime. A similar finding was observed in the direction of causality between natural gas consumption and CO2 emissions. While MS-GC determined unidirectional causality from natural gas consumption to environmental pollution in the first regime, a bidirectional causality result between GC and environmental pollution was determined in the second regime. The FGC result was similar to the second regime result. And lastly, the MS-GC and FGC methods determined unidirectional causality from Industry 4.0 to environmental pollution.
Keywords: Industry 4; 0; sustainability; natural gas consumption; environmental pollution; MS-VAR; MS-Granger causality; Fourier Granger causality; Fourier VAR; ENERGY-CONSUMPTION; ECONOMIC-GROWTH; OIL; GDP; COINTEGRATION; TECHNOLOGIES; OUTPUT; INDIA; CHINA; Science & Technology - Other Topics; Environmental Sciences & Ecology